Trees shape the soil microbiome of a temperate agrosilvopastoral and syntropic agroforestry system - Anna Vaupel; Max Küsters; Julia Toups; Nadine Herwig; Benedikt Bösel; Lukas Beule (Scientific Reports)
Abstract Agroforestry systems are multifunctional land-use systems that promote soil life. Despite their large potential spatio-temporal complexity, the majority of studies that investigated soil organisms in temperate cropland agroforestry systems focused on rather non-complex systems. Here, we investigated the topsoil and subsoil microbiome of two complex and innovative alley cropping systems: an agrosilvopastoral system combining poplar trees, crops, and livestock and a syntropic agroforestry system combining 35 tree and shrub species with forage crops. Increasing soil depth resulted in a decline of bacterial and fungal richness and a community shift towards oligotrophic taxa in both agroforestry systems, which we attribute to resource-deprived conditions in subsoil. At each soil depth, the microbiome of the tree rows was compositionally distinct from the crop rows. We detected a shift towards beneficial microorganisms as well as a decline in putative phytopathogens under the trees as compared to the crop rows. Finally, based on our results on community dissimilarity, we found that compared to an open cropland without trees, spatial heterogeneity introduced by the tree rows in the agrosilvopastoral system translated into a compositionally less homogeneous soil microbiome, highlighting the potential of agroforestry to counteract the homogenization of the soil microbiome through agriculture.